Malaysian evidence supporting theoretical integration of roles of non-executive directors - Hairul Azlan Annuar (Emerald Publishing Limited, 2018)
The purpose of this paper is to investigate the role of independent non-executive directors (INEDs) in Malaysian public listed companies (PLCs), other than the control role prescribed by agency theory and reformatory documents such as the Malaysian Code of Corporate Governance.A qualitative research design, consisting of face-to-face interviews with 27 company directors of Malaysian-owned PLCs, was instigated.The interviews revealed that INEDs do more than just monitor their executive counterparts. Apart from the control role, INEDs of Malaysian companies provide a conduit for mitigating uncertainties in the environment and perform invaluable services to the host companies.This research utilized interviews. Generalizations may be an issue when interviews are used as the method of inquiry. Also, the sample is not random as access to many of the interviewed directors depended on recommendations. In addition, respondents were consciously selected in order to obtain various board positions that include independent and non-independent directors.There are limited studies using qualitative research design in investigating INEDs’ performing other roles apart from the control role of the board in developing countries. Many of previous studies and literature in this area of corporate governance were predominantly based upon experiences of western economies.